Turmeric Topical Application: An effective solution for reducing breast milk secretion delays in new mothers - Ariestini, Tri Ratna; Aden, Christine; Berthiana, Berthiana; Mashar, Harlyanti Muthma'innah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: The problem of low coverage of exclusive breastfeeding is partly influenced by insufficient breast milk production. The percentage of exclusive breastfeeding in infants under six months of age in Central Kalimantan in 2020 was 52.98%. This percentage was among the lowest nationally. In 2021, the coverage of exclusive breastfeeding in infants under six months of age reached 56.8%, and in 2022 it did 60.5%. The figure in 2022 exceeded the set target, but several regencies/cities still had low coverage. Insufficient breast milk supply impacts on the nutritional status of the child. Low breast milk production also arises due to several other factors during breastfeeding, namely late initiation of breastfeeding, long breastfeeding time, sore nipples, breast pain and swelling, and inverted nipples. Aims: The study sought to measure the level of success of turmeric topical application in shortening the time it takes to initiate breast milk secretion. Methods: The study uses a true experimental posttest-only control group design. A subject of 50 mothers having full-term spontaneous deliveries and with normal breasts was used in the study. The sample was divided into two groups: control and intervention groups. The sample was selected using a matching process based on age, parity, and early initiation of breastfeeding. Subjects who met the inclusion criteria were offered whether they were willing to be given turmeric compresses after the delivery process. Subjects who were willing were included in the intervention group and those who were not willing were included in the control group. Age and parity in the intervention group were all taken, while the control group was selected to match the intervention group. The intervention group was given a treatment with a turmeric compress on the breasts for six hours. All participants were then observed for time of breast milk secretion initiation. In this experiment, we didn't perform blinding, but we managed it by having the midwife administer the turmeric compress just once during the delivery process before sending the client home. Following this, we recorded the results, specifically the initial breast milk release in both the intervention and the control group. Results: The average time periods it took to initiate breast milk secretion in the intervention and control groups were 509.96 minutes (8.5 hours) and 1573.76 minutes (26.2 hours), respectively. There was a significant difference (p = 0.023) in the time of breast milk secretion initiation of 1063.8 minutes or 17.73 hours between both groups. Conclusion: Applying a turmeric compress on the breasts of postpartum mothers may shorten the time it takes to initiate breast milk secretion. Received: 05 August 2024, Reviewed: 23 August 2024, Revised: 21 September 2024, Accepted: 13 October 2024.